2006
DOI: 10.1002/jclp.20297
|View full text |Cite
|
Sign up to set email alerts
|

Daily interpersonal events in pain patients: Applying action theory to chronic illness

Abstract: Action theory proposes that individuals actively shape and then respond to their environments, highlighting the role of stable person characteristics in the development and maintenance of life's interpersonal difficulties. In this study, we adopted the action perspective in our examination of the daily lives of chronic pain patients with rheumatoid arthritis. Our evaluation of patients' daily diary reports indicated that individuals played a more prominent role in shaping their positive versus their negative s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 49 publications
1
13
0
Order By: Relevance
“…This translates into an r of 0.45 or a Cohen's d of 1, which is a medium to large effect. Smaller effect sizes are consistent with effect sizes in other EMA research . There was insufficient variability in several of the daily patterns that prevented us from testing the moderating effect of diagnosis, sex, and age on the interaction between fatigue and physical activity.…”
Section: Discussionsupporting
confidence: 85%
“…This translates into an r of 0.45 or a Cohen's d of 1, which is a medium to large effect. Smaller effect sizes are consistent with effect sizes in other EMA research . There was insufficient variability in several of the daily patterns that prevented us from testing the moderating effect of diagnosis, sex, and age on the interaction between fatigue and physical activity.…”
Section: Discussionsupporting
confidence: 85%
“…In a longitudinal study (), fatigue was also associated with minor negative work place events (commonly occurring stressful events), but not with major work place events. In another longitudinal study (), fatigue turned out to be related to same day negative daily events, positive daily events, stress with friends, stress with family, enjoyment with family, and enjoyment with the spouse, but not to enjoyment with friends, stress or enjoyment with coworkers, or stress with the spouse (). A cross‐sectional study about the impact of fatigue on parenting found that fatigue was related to greater frequency and intensity of daily hassles while parenting as well as having less energy to monitor a child's whereabouts ().…”
Section: Resultsmentioning
confidence: 99%
“…The personality trait of extraversion may also play a prominent role in resilience by increasing the frequency of beneficial social interactions [46]. What may be most important, however, is that the occurrence of positive social interactions does not seem to be tied very closely to fluctuations in pain or disease behavior; instead, social engagement appears more to be a function of personal characteristics and social opportunity that may potentially be improved through psychological and social intervention [47]. Thus, those individuals who learn to sustain positive social relationships and secure social support seem to demonstrate a higher level of adaptation to pain.…”
Section: Social Resilience Resources and Mechanismsmentioning
confidence: 99%